2021
DOI: 10.1515/reveh-2020-0107
|View full text |Cite
|
Sign up to set email alerts
|

Occupational hazard in Malaysian traffic police: special focus on air pollutants

Abstract: This paper provides a specific deliberation on occupational hazards confronted daily by Malaysian Traffic Police. Traffic police is a high-risk occupation that involves a wide range of tasks and, indirectly, faced with an equally wide variety of hazards at work namely, physical, biological, psychosocial, chemical, and ergonomic hazards. Thereupon, occupational injuries, diseases, and even death are common in the field. The objective of this paper is to collate and explain the major hazards of working as Malays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Therefore, skin, respiratory, and eye problems were the most common physical problems seen among traffic police reported in another study in Kathmandu [ 13 ]. A Malaysian study reported that traffic police experience hypo- or hyperthermia, skin cancer, depression, lower back pain, asthma, NIHL, and so forth due to occupational exposure to major environmental hazards [ 14 ]. A study conducted in Hong Kong has assessed that 80% of traffic constables have reported exposure to environmental tobacco smoke, and the odds ratio of having respiratory systems is 20.4 times more in men as compared to women [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, skin, respiratory, and eye problems were the most common physical problems seen among traffic police reported in another study in Kathmandu [ 13 ]. A Malaysian study reported that traffic police experience hypo- or hyperthermia, skin cancer, depression, lower back pain, asthma, NIHL, and so forth due to occupational exposure to major environmental hazards [ 14 ]. A study conducted in Hong Kong has assessed that 80% of traffic constables have reported exposure to environmental tobacco smoke, and the odds ratio of having respiratory systems is 20.4 times more in men as compared to women [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…About 73% of traffic police were reported with anxiety, while stress-related problems were identified among 40.6% in another study conducted in Kathmandu [ 13 ]. Poor pay, workload, and irregular working hours were stress factors causing psychological hazards among Malaysian traffic police [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their nature of work, they are frequently exposed to stressful conditions that lead to burnout, anxiety, and post-traumatic stress disorder (PTSD). The psychological challenges that traffic police officers have been brought to light by previous studies, which also emphasized the necessity of having supportive measures, such as counselling services and stress management programs (3)(4).…”
Section: Occupational Hazards and Health Risksmentioning
confidence: 99%
“…Traffic police are an outdoor occupational group that have high chronic exposure to TRAP. Prior studies investigating the health effects of TRAP exposure have focused on the respiratory effects [28][29][30][31][32][33][34], mutagenic and carcinogenic effects [35][36][37][38][39], cytotoxic effects [40][41][42][43][44], chromosomal damage [45], lipid metabolism [46,47], inflammatory effects [48,49], cardiovascular effects [50,51], nephrotoxicity [52], exposure to toxic metals [53][54][55], and physical and psychological hazards [56]. However, published studies of traffic police are lacking that examine the effects of chronic TRAP exposure on CVD biomarkers such as CIMT.…”
Section: Introductionmentioning
confidence: 99%